Involvement of p59fynT in interleukin-5 receptor signaling [published erratum appears in J Exp Med 1995 Oct 1;182(4):1179] (The Rockefeller University Press, 1995)
Previous studies implicate the nonreceptor protein tyrosine kinase (PTK) p59fyn in the propagation of signals from the B cell antigen receptor. To elucidate the functions of this kinase, we examined B cell responsiveness in mice engineered to lack the hematopoietic isoform of p59fyn. Remarkably, antigen receptor signaling was only modestly defective in fynTnull B cells. In contrast, signaling from the interleukin (IL)-5 receptor which ordinarily provides a comitogenic stimulus with antiimmunoglobulin, was completely blocked. Our results document the importance of p59fynT in IL-5 responses in B cells, and they support a general model for cytokine receptor signal transduction involving the simultaneous recruitment of at least three families of PTK.